Crystal structure of 2,4-diamino-7-(hydroxymethyl)pteridin-1-ium nitrate - Sivajeyanthi, Palaniyappan; Balasubramani, Kasthuri; Jeevaraj, Muthaiah; Thanigaimani, Kaliyaperumal; Khalib, Nuridayanti Che; Razak, Ibrahim Abdul (International Union of Crystallography, 2015)
In the crystal of the title molecular salt, C7H9N6O+ NO3, the cations and anions are linked via N—HO and O—HO hydrogen bonds, forming sheets parallel to (100). Within the sheets there are numerous hydrogen-bonding ring motifs.